Centrifugal cast composite rolls for hot rolling
By optimizing the composition of the centrifugal cast composite roll with specific ranges of C, Si, Mn, Ni, Cr, Mo, V, and Nb, the issues of abrasion resistance, casting defects, and boundary integrity are addressed, resulting in a roll with enhanced performance for hot rolling applications.
Patent Information
- Application Number
- JP2021552475
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-16
- Filing Date
- 2020-10-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-10-16
AI Technical Summary
Existing centrifugal cast composite rolls for hot rolling face challenges with abrasion resistance, casting defects, and a sound boundary between the outer and inner layers, particularly due to imbalances in the distribution of MC carbides and excessive content of certain elements.
The composition of the centrifugal cast composite roll is optimized with C: 2.6 to 3.6%, Si: 0.1 to 3%, Mn: 0.3 to 2%, Ni: 2.3 to 5.5%, Cr: 0.5 to 3.2%, Mo: 0.3 to 1.6%, V: 1.8 to 3.4%, and Nb: 0.7 to 2.4%, with specific ratios of V/Nb and V equivalent (Veq) to ensure uniform distribution of MC carbides across the rolling area and a healthy boundary between layers.
This optimized composition achieves excellent abrasion resistance across the entire rolling area, suppresses casting defects, and maintains a sound boundary between the outer and inner layers, making the composite roll suitable for use in finishing rolling mills for hot strip mills.
Smart Images

Figure 0007666328000005 
Figure 0007666328000006 
Figure 0007666328000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a centrifugally cast composite roll suitable for use in, particularly, the fifth to seventh stands of a hot rolling mill for steel plate, and more particularly to a centrifugally cast composite roll for hot rolling which has good wear resistance over the entire rolling range, inhibits the occurrence of casting defects, and has a sound boundary between an outer layer and an inner layer. [Background technology]
[0002] In a hot strip mill, a slab with a thickness of several tens to 300 mm produced by continuous casting or the like is heated, and then passed between the rolls of several rough rolling mills and several finishing rolling mills in sequence, and rolled to a thickness of about 1 mm to several tens of mm. A finishing mill is usually a four-high rolling mill stand arranged in series, and a finishing mill consisting of seven stands is particularly widely used. In a seven-stand finishing mill, the first to third stands are called the front stands, and the fourth to seventh stands are called the rear stands.
[0003] Rolls used in finishing mills must withstand thermal and mechanical loads caused by rolling, so centrifugally cast composite rolls (sometimes simply called "composite rolls") are used, which have a composite structure in which an outer layer with excellent wear resistance and an inner layer with excellent toughness are welded together. However, because the thermal and mechanical loads caused by rolling cause damage such as wear, roughness, and heat cracks on the surface of the outer layer, the composite roll is removed from the rolling mill after a certain period of use and the damage is ground off (reground). By grinding, the body diameter of the composite roll gradually decreases from the initial diameter to the minimum diameter (discard diameter) that can be used for rolling. In this specification, the roll diameter from the initial diameter to the discard diameter is called the effective diameter for rolling (simply called the "effective diameter"), and the effective diameter region from the initial diameter to the discard diameter is called the "use region."
[0004] In the case of a finishing rolling mill, particularly in the latter stands, a centrifugally cast composite roll, in which an outer layer made of high-alloyed chromium cast iron and an inner layer made of tough cast iron are metallurgically integrated, has been conventionally used. The high-alloyed chromium cast iron outer layer consists of graphite, carbides and a matrix structure, and is particularly excellent in seizure resistance. Therefore, even when a choking accident occurs, the generation and progression of cracks are extremely small, that is, it has excellent accident resistance. Especially in the latter stands, since choking accidents often occur due to the rolling of thin steel plates stacked on top of each other, composite rolls with a high-alloyed chromium cast iron outer layer with good accident resistance are often used. High-alloyed chromium cast iron includes a type containing only M3C (cementite) and a type containing a relatively small amount of MC carbides composed of elements such as M3C (cementite) and vanadium to improve wear resistance. However, since high-alloyed chromium cast iron is inferior in wear resistance compared to high-chromium cast iron materials and high-speed steel materials, various improvements have been made.
[0005] Japanese Patent Application Laid-Open No. 2004-68142 discloses a hot rolling composite roll outer layer material used for the outer layer, which contains, by mass, C: 2.9 to 3.8%, Si: 0.8 to 2.0%, Mn: 0.2 to 1.5%, Cr: 1.5 to 3.5%, Mo: 0.8 to 3.5%, Ni: 3.0 to 7.0%, V: 1.0 to 3.5%, Nb: 0.1 to 0.8%, B: 0.020 to 0.2%, REM: 0.002 to 0.030%, and satisfies the formula (1): [2.5 ≤ C - (0.236 × V + 0.129 × Nb) ≤ 3.2], and the formula (2): [0.5 < Cr / C < 1.0], and has a composition consisting of the balance Fe and inevitable impurities. Japanese Patent Application Laid-Open No. 2004-68142 describes that a composite roll having this outer layer material has excellent seizure resistance and wear resistance and is suitable for a roll for the latter stand in hot rolling of steel plates.
[0006] Among the specific examples described in JP 2004-68142 A, (1) test material L containing 3.76% C, 1.67% Cr, 2.38% V, 0.92% Nb, 4.62% Ni, 1.64% Si, 0.54% Mn, 1.30% Mo, 0.054% B, and 0.011% REM has a problem that the C content is as high as 3.76%, which results in an excess of graphite and carbides, resulting in reduced strength and toughness, and (2) Test material T, which contains 3.46% C, 2.27% Cr, 2.46% V, 0.83% Nb, 4.55% Ni, 1.78% Si, 0.61% Mn, 0.66% Mo, 0.042% B, and 0.019% REM, has a problem in that the distribution of MC carbides is biased toward the inner periphery of the outer layer due to the V / Nb ratio being too large at 2.96. (3) Test material W, which contains 3.35% C, 1.97% Cr, 3.27% V, 1.57% Nb, 4.61% Ni, 1.91% Si, 0.5% Mn, 1.32% Mo, and 0.074% B, has a high V equivalent (Veq = V + 0.55Nb) of 4.13 mass%, which results in a large amount of MC carbides, and causes problems such as uneven structure and coarsening of the structure.
[0007] Japanese Patent Laid-Open No. 2001-279367 discloses a centrifugally cast roll for hot rolling, which comprises an outer layer made of high alloy grain cast iron, the outer layer being made of, by mass, 2.7-4.0% C, 0.5-2% Si, 0.2-2% Mn, 0.2-0.8% Mo, 2.5-6.0% Ni, 1.0-2.0% Cr, 0.01-0.1% B, and one or two of 0.2-1.0% Nb and 0.2-2.0% V, with the balance being Fe and unavoidable impurities, and an inner layer made of high-grade cast iron or spheroidal graphite cast iron. In the outer layer of this centrifugally cast roll, appropriate amounts of Nb and V are added to the basic composition of conventional high alloy grain cast iron material, and appropriate amounts of B etc. are also added, so that the carbides formed are mainly M3C type (cementite), MC carbides are small, about 3% or less, and fine graphite particles are uniformly distributed in the cast structure. JP 2001-279367 A provides a hot rolling roll that has excellent wear resistance and crack resistance without containing a large amount of expensive alloys, at low cost, by centrifugal casting.
[0008] JP 2001-279367 A describes, as a specific example of the outer layer, test material 11 containing 3.2% C, 2.4% Si, 0.8% Mn, 0.6% Mo, 4.2% Ni, 2.2% Cr, 1.5% Nb, 3.5% V, and 0.04% B. However, in test material 11, not only does the V content of 3.5%, which is too high, tend to cause MC carbides to be biased toward the inner periphery of the outer layer, but also the amount of MC carbides is high because Veq is 4.33 mass%, making the structure uneven and coarsening likely to occur.
[0009] JP 2008-50681 A discloses an outer layer material for a centrifugally cast composite roll for rolling, which contains, by mass, 2.5-3.4% C, 0.5-2.0% Si, 0.5-1.0% Mn, 3.0-6.0% Ni, 1.0-2.0% Cr, 0.2-0.8% Mo, 1.0-4.0% V, and 0.2-1.0% Nb, with the mass percentages of V and Nb satisfying formula (1): 1≦(V-1) / Nb≦4 and formula (2): 0.7≦1.8(V-1)+Nb≦5.0, with the balance being Fe and unavoidable impurities. JP 2008-50681 A describes that this outer layer material has excellent wear resistance and is free from surface roughness due to gravity segregation and crystallization of coarse MC carbides.
[0010] JP 2008-50681 A describes, as specific examples, (1) an outer layer test piece containing 3.1% C, 1.8% Si, 0.8% Mn, 4.5% Ni, 1.1% Cr, 0.3% Mo, 3.0% V, 1.0% Nb, and 0.03% B; (2) an outer layer test piece containing 3.2% C, 1.8% Si, 0.6% Mn, 4.1% Ni, 1.2% Cr, 0.8% Mo, 2.0% V, and 1.0% Nb; and (3) an outer layer test piece containing 3.5% C, 1.1% Si, 0.4% Mn, 2.9% Ni, 1.9% Cr, 0.2% Mo, 2.0% V, and 1.2% Nb. However, the test piece (1) has a problem in that the distribution of MC carbides is biased toward the inner periphery of the outer layer because the V / Nb ratio is too large at 3. Also, the test pieces (2) and (3) not only do not contain B, but the test piece (2) has poor wear resistance because its Veq is too low at 2.55 mass%, and the test piece (3) has insufficient hardenability because its Mo content is too low at 0.2%, resulting in low matrix hardness and poor wear resistance and accident resistance.
[0011] JP 2017-185548 A discloses a steel sheet having an outer layer containing, by mass, 2.6-3.8% C, 0.1-3.0% Si, 0.3-2.0% Mn, 2.3-5.5% Ni, 0.5-2.5% Cr, 0.2-3.0% Mo, 0.2-3.8% V, 0.4-6.8% Nb, and the remainder being Fe and unavoidable impurities, and having a structure containing 0.3-10% graphite particles by area, and a shaft core portion made of ductile cast iron, in which the C content at positions 100 mm away from both end faces of the outer layer in the axial direction is 0.05-0.3% higher by mass than the C content at the center of the axial length of the outer layer, and .... The present invention discloses a centrifugally cast composite roll for hot rolling, in which the Nb content at a position 0.5 to 3.0 mass % away from the center of the axial length of the outer layer is higher than the Nb content at the center of the axial length of the outer layer by 0.5 to 3.0 mass %. This roll has an outer layer that can reduce local wear of the outer layer so that wear progresses evenly between the outer layer center portion facing the width center portion of the steel sheet to be rolled and the outer layer ends facing the vicinity of the width ends on both sides of the steel sheet. Since the outer layer wears evenly in the roll axial direction, when the roll is used for rolling again, the loss of polishing until the locally worn portions disappear during roll polishing is suppressed to a small amount, and loss of outer layer material can be reduced.
[0012] As a specific example in JP 2017-185548 A, the outer layer of Example 1 has a composition containing C: 3.34%, Si: 1.3%, Mn: 0.81%, Ni: 4.12%, Cr: 1.86%, Mo: 0.82%, V: 2.33%, and Nb: 0.78%, and the outer layer of Example 2 has a composition containing C: 3.51%, Si: 1.45%, Mn: 0.65%, Ni: 4.51%, Cr: 1.58%, Mo: 0.64%, V: 2.55%, and Nb: 0.92%. However, in both examples, V / Nb is too large at 2.99 and 2.77, so the distribution of MC carbides tends to be biased toward the inner periphery of the outer layer, the yield of MC carbides in the use layer decreases, and the wear resistance deteriorates.
[0013] JP 2003-73767 A discloses an outer layer material for a hot rolling roll, which contains, by mass%, 2.5-4.0% C, 0.8-2.5% Si, 0.2-1.5% Mn, 1.0-3.5% Cr, 0.5-4.0% Mo, 3.0-7.0% Ni, 1.0-3.5% V, 0.2-1.0% Nb, 0.02-0.2% Al, and 0.020-0.10% B, with a Cr / C ratio of 1 or less, the remainder being Fe and unavoidable impurities, and has a structure containing 0.6-4% graphite by area ratio. As a specific example described in JP 2003-73767 A, ring material D has a composition containing 2.6% C, 1.7% Si, 0.5% Mn, 4.9% Ni, 3.0% Cr, 1.2% Mo, 1.8% V, 1.3% Nb, 0.081% Al, and 0.046% B. However, this ring material D has a V / Nb ratio of 1.38, which is too small, and a Veq of 2.52, which is too small.
[0014] JP 2015-193025 A discloses a composite roll for rolling having an outer layer containing, by mass, C: 3.0-4.5%, Si: more than 0% and not more than 2.0%, Mn: more than 0% and not more than 1.5%, Ni: 3.0-5.0%, Cr: 1.4-4.0%, Mo: 0.1-3.0%, and V: more than 0% and not more than 3.0%, with the remainder being Fe and unavoidable impurities, and having a composition that satisfies the condition 4.0%≦C+Si / 3+Cr / 7.5≦5.5%, and having an area ratio of cementite in the metal structure of the peripheral surface of the outer layer being 40-60%. As a specific example described in JP 2015-193025 A, the outer layer of No. 1 has a composition containing 3.7% C, 1.3% Si, 0.8% Mn, 4.0% Ni, 2.1% Cr, 0.2% Mo, 2.1% V, 1.2% Nb, and 0.05% B. However, because the C content is too high at 3.7% and the Mo content is too low at 0.2%, there are problems in that the amount of carbide is excessive, which reduces crack resistance, and the hardenability is insufficient, the matrix hardness is insufficient, and the wear resistance and surface roughening resistance are poor.
[0015] JP 2015-080813 A discloses a centrifugally cast composite roll for rolling having an outer layer and an inner layer, in which the chemical components of the outer layer are, by mass ratio, C: 1.5-4.0%, Si: 0.5-3.0%, Mn: 0.1-1.5%, Ni: 1.0-6.0%, Cr: 0.1-3.0%, Mo: 0.1-3.0%, and V: 1.0-6.0%, with the remainder being Fe and unavoidable impurities, and which satisfies 4.0≦V+C≦8.0 and 0.2≦Si / (Cr+2V)≦0.3. As a specific example described in JP 2015-080813 A, the outer layer of No. 8 has a composition containing 3.4% C, 1.6% Si, 0.8% Mn, 4.5% Ni, 1.8% Cr, 0.5% Mo, 2.5% V, 0.9% Nb, and 0.04% B. However, because the V / Nb ratio is too large at 2.78, the distribution of MC carbides tends to be biased toward the inner periphery of the outer layer, and the soundness of the boundary between the outer layer and the inner layer is insufficient. Summary of the Invention [Problem to be solved by the invention]
[0016] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a centrifugally cast composite roll for hot rolling which has good wear resistance over the entire rolling range, suppresses the occurrence of casting defects, and has a sound boundary between the outer layer and the inner layer. [Means for solving the problem]
[0017] As a result of intensive research in consideration of the above object, the present inventors have discovered that, in the outer layer of a hot rolling composite roll used in a hot strip mill, by optimizing the composition of constituent elements including V and Nb so that MC carbides contributing to wear resistance are distributed mainly in the usage region from the initial diameter to the discard diameter, and by limiting the V / Nb ratio and V equivalent (Veq=V+0.55Nb) to a predetermined range, it is possible to obtain an outer layer having relatively uniformly excellent wear resistance in the usage region, suppressing the occurrence of casting defects, and having a sound boundary with the inner layer, and have arrived at the present invention.
[0018] That is, the centrifugally cast composite roll for hot rolling of the present invention is characterized in that it contains, by mass, 2.6-3.6% C, 0.1-3% Si, 0.3-2% Mn, 2.3-5.5% Ni, 0.5-3.2% Cr, 0.3-1.6% Mo, 1.8-3.4% V, and 0.7-2.4% Nb, with 1.4≦V / Nb≦2.7, a V equivalent (Veq=V+0.55Nb) of 2.60-4 mass%, and the remainder being Fe and impurities, and an inner layer made of an iron-based alloy is welded and integrated with the outer layer made of an Fe-based alloy having a chemical composition.
[0019] In the centrifugally cast composite roll for hot rolling of the present invention, it is preferable that the outer layer further contains B: 0.06% by mass or less.
[0020] In the centrifugally cast composite roll for hot rolling of the present invention, the outer layer preferably further contains, by mass, any one or more of W: 0.01-3%, Ti: 0.01-0.5%, Al: 0.001-0.5%, Zr: 0.01-0.5%, and Co: 0.1-5%.
[0021] In the centrifugally cast composite roll for hot rolling of the present invention, the V equivalent of the outer layer is preferably 3.8 mass % or less.
[0022] In the centrifugally cast composite roll for hot rolling of the present invention, the outer layer preferably contains, by area, 0.3 to 5% of graphite particles and 2 to 20% of MC carbides. Effect of the Invention
[0023] The outer layer of the centrifugally cast composite roll for hot rolling of the present invention contains 1.8 to 3.4 mass% V and 0.7 to 2.4 mass% Nb, and satisfies the conditions of 1.4≦V / Nb≦2.7 and V equivalent (Veq=V+0.55Nb) of 2.60 to 4 mass%, so that the outer layer has excellent wear resistance in both the surface layer and the deep part, the occurrence of casting defects is suppressed, and the boundary with the inner layer (intermediate layer if there is an intermediate layer) is sound. Therefore, the centrifugally cast composite roll for hot rolling of the present invention is suitable for use in the finishing rolling mill of a hot strip mill.
[0024] The centrifugally cast composite roll for hot rolling of the present invention is suitable for use as a work roll for a hot strip mill under severe rolling conditions, but can also be used as a hot rolling roll for wire rods, hot rolling roll for shaped steel, etc. [Brief description of the drawings]
[0025] [Figure 1] 1 is a schematic cross-sectional view showing a centrifugally cast composite roll for hot rolling of the present invention. [Diagram 2] 1 is a graph showing a schematic distribution of MC carbides in a used region of an outer layer. [Figure 3(a)] FIG. 2 is an exploded cross-sectional view showing an example of a mold used in the manufacture of a centrifugally cast composite roll for hot rolling according to the present invention. [Figure 3(b)] FIG. 2 is a cross-sectional view showing an example of a mold used in the manufacture of a centrifugally cast composite roll for hot rolling according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The embodiments of the present invention will be described in detail below, but the present invention is not limited thereto, and various modifications may be made within the scope of the technical idea of the present invention. Unless otherwise specified, when simply written as "%", it means "% by mass".
[0027] [1] Centrifugal cast composite rolls for hot rolling Fig. 1 shows a composite roll 10 for hot rolling, which is composed of an outer layer 1 formed by a centrifugal casting method and an inner layer 2 integrally welded to the outer layer 1. The inner layer 2 has a trunk core portion 21 welded to the outer layer 1, and shaft portions 22 and 23 extending integrally from both ends of the trunk core portion 21.
[0028] (A) Outer layer (i) Composition The composition of the outer layer of the centrifugally cast composite roll for hot rolling of the present invention is represented by the composition of the iron-based alloy melt used to form the outer layer. The composition of the iron-based alloy melt corresponds to the average composition of the entire outer layer. The Fe-based alloy forming the outer layer basically belongs to the category of "high alloy grain cast iron".
[0029] (a) Essential elements (1) C: 2.6~3.6% by mass C combines with V, Nb, Cr, and Mo to form hard carbides, which contribute to improving wear resistance. It also crystallizes as graphite in the structure due to graphitization-promoting elements such as Si and Ni, thereby imparting seizure resistance to the outer layer and improving the toughness of the outer layer. If C is less than 2.6 mass%, not only is the crystallization of graphite insufficient, but the amount of crystallization of hard carbides is too small to impart sufficient wear resistance to the outer layer.
[0030] On the other hand, if the C content exceeds 3.6% by mass, the graphite becomes excessive and the shape becomes string-like, decreasing the strength of the outer layer. In addition, the amount of crystallization of carbide becomes excessive, decreasing the toughness of the outer layer and decreasing the crack resistance, so that the cracks caused by rolling become deeper and the roll loss increases. The lower limit of the C content is preferably 2.7% by mass, more preferably 2.8% by mass. The upper limit of the C content is preferably 3.5% by mass, more preferably 3.4% by mass. One example of a preferred range of the C content is 2.7 to 3.5% by mass, and one example of a more preferred range is 2.8 to 3.4% by mass.
[0031] (2) Si: 0.1~3% by mass Silicon reduces oxide defects by deoxidizing the molten metal and promotes the crystallization of graphite, contributing to improved seizure resistance and suppression of crack growth. If the Si content is less than 0.1% by mass, the deoxidization of the molten metal is insufficient and the crystallization of graphite is also insufficient. On the other hand, if the Si content exceeds 3% by mass, the alloy matrix becomes embrittled and the toughness of the outer layer decreases. The lower limit of the Si content is preferably 0.5% by mass, more preferably 1% by mass. The upper limit of the Si content is preferably 2.8% by mass, more preferably 2.5% by mass. An example of a preferred range of the Si content is 0.5 to 2.8% by mass, and an example of a more preferred range is 1 to 2.5% by mass.
[0032] (3) Mn: 0.3~2% by mass Mn has the effect of deoxidizing the molten metal and also fixes the impurity S as MnS. If the Mn content is less than 0.3 mass%, these effects are insufficient. On the other hand, if the Mn content exceeds 2 mass%, no further effects are obtained. The lower limit of the Mn content is preferably 0.4 mass%, more preferably 0.5 mass%. The upper limit of the Mn content is preferably 1.5 mass%, more preferably 1 mass%. An example of a preferred range of the Mn content is 0.4 to 1.5 mass%, and an example of a more preferred range is 0.5 to 1 mass%.
[0033] (4) Ni: 2.3~5.5% by mass Ni has the effect of crystallizing graphite, and contributes to seizure resistance. Ni also has the effect of improving the hardenability of the matrix structure. If Ni is less than 2.3 mass%, this effect cannot be obtained sufficiently. On the other hand, if Ni is more than 5.5 mass%, austenite becomes too stabilized, and it becomes difficult to transform into bainite or martensite. The lower limit of the Ni content is preferably 2.5 mass%, more preferably 3 mass%, and even more preferably 3.5 mass%. The upper limit of the Ni content is preferably 5 mass%, and more preferably 4.8 mass%. An example of a preferred range of the Ni content is 2.5 to 5 mass%, an example of a more preferred range is 3 to 4.8 mass%, and an example of a more preferred range is 3.5 to 4.8 mass%.
[0034] (5) Cr:0.5~3.2% by mass Cr is an element that improves hardenability, and is effective in maintaining hardness and wear resistance by forming the matrix into bainite or martensite. If the Cr content is less than 0.5 mass%, the effect of adding the Cr content is insufficient. On the other hand, if the Cr content exceeds 3.2 mass%, not only does it inhibit the crystallization of graphite, but it also forms coarse eutectic carbides, which reduces the toughness of the matrix structure. The lower limit of the Cr content is preferably 0.7 mass%, more preferably 1 mass%. The upper limit of the Cr content is preferably 2.8 mass%, more preferably 2.5 mass%, and even more preferably 2.3 mass%. An example of a preferred range of the Cr content is 0.7 to 2.8 mass%, an example of a more preferred range is 1 to 2.5 mass%, and an example of a more preferred range is 1 to 2.3 mass%.
[0035] (6) Mo: 0.3~1.6% by mass Mo combines with C to form hard Mo carbides, which increase the hardness of the outer layer and improve the hardenability of the matrix. If Mo is less than 0.3 mass%, these effects are insufficient. On the other hand, if Mo exceeds 1.6 mass%, the toughness of the outer layer deteriorates and the tendency to whiten increases, inhibiting the crystallization of graphite. The lower limit of the Mo content is preferably 0.4 mass%. The upper limit of the Mo content is preferably 1.3 mass%, more preferably 1 mass%. An example of a preferred range of the Mo content is 0.4 to 1.3 mass%, and an example of a more preferred range is 0.4 to 1 mass%.
[0036] (7) V:1.8~3.4% by mass V is an element that combines with C to produce hard MC carbides. When V is less than 1.8% by mass, the amount of crystallization of MC carbides is insufficient. On the other hand, when V is more than 3.4% by mass, (a) the VC carbides, which have a low specific gravity, are concentrated on the inside of the outer layer due to the centrifugal force during centrifugal casting, and the range in which the distribution of MC carbides is maximum is shifted from the region from the initial diameter to the discard diameter of the outer layer, and (b) the MC carbides are coarsened, the alloy structure becomes coarse, and the surface becomes rough during rolling. The lower limit of the V content is preferably 1.85% by mass, more preferably 1.9% by mass. The upper limit of the V content is preferably 3% by mass, more preferably 2.7% by mass, and most preferably 2.5% by mass. An example of a preferred range of the V content is 1.85 to 3% by mass, an example of a more preferred range is 1.9 to 2.7% by mass, and an example of an even more preferred range is 1.9 to 2.5% by mass.
[0037] (8) Nb: 0.7~2.4% by mass Nb combines with C to produce MC carbides. By combining Nb with V, (a) it dissolves in the MC carbides to strengthen them and improve the wear resistance of the outer layer, and (b) it increases the specific gravity of the MC carbides and prevents the MC carbides from segregating to the inner periphery of the outer layer. If the Nb content is less than 0.7% by mass, these effects are insufficient. On the other hand, if the Nb content exceeds 2.4% by mass, the specific gravity of the MC carbides becomes too large, and the distribution of the MC carbides becomes too large in the removal region from the outer periphery to the initial diameter. In addition, since oxides and flux in the molten metal tend to adhere to NbC, the oxides and flux adhered to NbC are easily trapped in the outer layer during solidification. Therefore, if the Nb content is too high, the risk of occurrence of casting defects due to the adhered oxides and flux increases. The lower limit of the Nb content is preferably 0.8% by mass, more preferably 0.9% by mass. The upper limit of the Nb content is preferably 2.2% by mass, more preferably 2.0% by mass. An example of a preferable range of the Nb content is 0.8 to 2.2 mass %, and an example of a more preferable range is 0.9 to 2.0 mass %.
[0038] (9) V / Nb: 1.4~2.7 In the outer layer formed by centrifugal casting of an iron-based alloy containing V and Nb, MC carbides consisting of VC and NbC are crystallized, but VC has a lower specific gravity than the outer layer molten metal and therefore tends to segregate on the inner peripheral side of the outer layer, while NbC has a higher specific gravity than the outer layer molten metal and therefore tends to segregate on the outer peripheral side of the outer layer. As shown in Fig. 2, the outer peripheral side of the centrifugally cast outer layer is cut and removed to the depth of the initial diameter Di (generally 10 mm), and then used from the initial diameter Di to a predetermined depth of the discard diameter Dd (for example, a depth of 50 mm from the initial diameter Di), so it is preferable that the MC carbides are mainly distributed in the use region (effective diameter region) from the initial diameter Di to the discard diameter Dd.
[0039] An example of such an MC carbide distribution is shown in FIG. 2. In MC carbide distribution I, the peak is located almost in the center of the use region, and there is a sufficient amount of MC on both the outer circumferential side (surface layer) and the inner layer side (deep part). In MC carbide distribution II, the peak is located near the initial diameter Di, but the amount of MC on both the outer circumferential side (surface layer) and the inner layer side (deep part) is sufficient. Both MC carbide distributions I and II are preferable. In contrast, in MC carbide distribution III, the peak located near the initial diameter Di is too high, and the amount of MC in the deep part is too low. Therefore, the wear resistance in the deep part of the outer layer is insufficient. In addition, in MC carbide distribution IV, the peak is located near the inner layer side, and there is not enough MC carbide in the use region. Therefore, the outer layer having MC carbide distribution IV cannot exhibit sufficient wear resistance. Therefore, both MC carbide distributions III and IV are not preferable.
[0040] NbC not only crystallizes from the molten metal at high temperatures, but also has a high affinity (good wettability) with oxides in the molten metal and oxidation prevention flux. Therefore, oxides and flux easily adhere to NbC. Oxides and flux that adhere to NbC are trapped in the outer layer during solidification, so they tend to remain in the outer layer as casting defects. In addition, NbC, which has a higher specific gravity than the molten metal, tends to be unevenly distributed on the outer periphery (surface layer) due to centrifugal separation, so casting defects caused by oxides and flux that adhere to NbC tend to appear more in the surface layer of the outer layer.
[0041] In order to suppress such a tendency, V and Nb must satisfy the condition of 1.4≦V / Nb≦2.7. If V / Nb is less than 1.4, the amount of crystallized primary NbC increases, making it difficult to suppress casting defects caused by oxides and flux attached to NbC. By satisfying the condition of 1.4≦V / Nb, it becomes possible to appropriately suppress the amount of crystallized NbC and prevent casting defects in the outer layer, especially in a molten metal with a V equivalent (Veq) of 2.60 mass% or more. The lower limit of V / Nb is preferably 1.45, more preferably 1.5.
[0042] On the other hand, when V / Nb exceeds 2.7, the proportion of VC with a low specific gravity increases, and MC carbides are segregated more on the inner peripheral side of the centrifugally cast outer layer, the distribution of MC carbides in the use region decreases, and they are concentrated on the inner peripheral side (deep part) of the outer layer. Since MC carbides with a high melting point are difficult to remelt during casting of the inner layer (intermediate layer if there is an intermediate layer), when Veq exceeds 2.6, the concentration of MC carbides in the deep part becomes significant, which inhibits the welding between the outer layer and the inner layer (intermediate layer if there is an intermediate layer) and impairs the soundness of the boundary between the two layers. The upper limit of V / Nb is preferably 2.65, more preferably 2.6. One example of a preferable range of V / Nb is 1.45 to 2.65, and one example of a more preferable range is 1.5 to 2.6.
[0043] (10) V equivalent: 2.60~4% by mass The amount of MC carbide formed in the outer layer can be expressed by V equivalent (Veq = V + 0.55Nb). The larger Veq is, the more MC carbide is crystallized. Veq is 2.60 to 4 mass%. If Veq is less than 2.60 mass%, the amount of MC carbide effective for wear resistance is too small. The lower limit of Veq is preferably 2.65 mass%, more preferably 2.7 mass%, and most preferably 2.8 mass%. On the other hand, if Veq becomes too large, cementite and graphite other than MC carbide become too small. In order to secure the required amount of cementite and graphite, it is sufficient to add C according to the MC carbide, but if too much C and Veq are added, the amount of MC carbide that solidifies earlier than the iron matrix becomes too large. If there is a lot of MC carbide in the liquid phase during solidification, segregation of MC carbide is likely to occur. For this reason, Veq is set to 4 mass% or less. Veq is preferably 3.8 mass% or less, more preferably 3.6 mass% or less, and most preferably 3.2 mass% or less. An example of a preferable range of the V equivalent is 2.65 to 3.8 mass%, an example of a more preferable range is 2.7 to 3.6 mass%, and an example of a most preferable range is 2.8 to 3.2 mass%.
[0044] (b) Arbitrary composition The outer layer of the centrifugally cast composite roll for hot rolling of the present invention may contain the following elements in addition to the above essential elements.
[0045] (1) B: 0.06% by mass or less B has the effect of refining carbides. Also, a small amount of B contributes to the crystallization of graphite. However, if B exceeds 0.06 mass%, the whitening effect becomes stronger and graphite becomes difficult to crystallize. Therefore, the B content is preferably 0.06 mass% or less. In order to obtain the effect of adding B, the lower limit of the B content is more preferably 0.001 mass%, and most preferably 0.002 mass%. The upper limit of the B content is more preferably 0.04 mass%. An example of a more preferable range of the B content is 0.001 to 0.04 mass%, and an example of a most preferable range is 0.002 to 0.04 mass%.
[0046] (2) W:0.01~3% by mass W combines with C to form hard M2C carbides, which contributes to improving the wear resistance of the outer layer. It also dissolves in MC carbides to increase their specific gravity and reduce segregation. However, if W exceeds 3 mass%, the specific gravity of the molten metal increases, making carbide segregation more likely to occur. Therefore, when W is added, its content is preferably 3 mass% or less. On the other hand, if W is less than 0.01 mass%, the effect of adding it is insufficient. The lower limit of the W content is more preferably 0.02 mass%. The upper limit of the W content is more preferably 2.9 mass%. One example of a more preferable range of the W content is 0.02 to 2.9 mass%.
[0047] (3) Zr:0.01~0.5% by mass Zr combines with C to form MC carbides, improving the wear resistance of the outer layer. Zr oxides formed in the molten metal act as crystal nuclei, resulting in fine solidification structures. It also increases the specific gravity of MC carbides to prevent segregation. However, if Zr exceeds 0.5 mass%, it is not preferable because inclusions are formed. Therefore, when Zr is added, its content is preferably 0.5 mass% or less. On the other hand, if Zr is less than 0.01 mass%, the effect of adding it is insufficient. The lower limit of the Zr content is more preferably 0.02 mass%. The upper limit of the Zr content is more preferably 0.4 mass%. One example of a more preferable range of the Zr content is 0.02 to 0.4 mass%.
[0048] (4) Co:0.1~5% by mass Co is an element effective in strengthening the matrix structure. Co also facilitates the crystallization of graphite. However, if Co exceeds 5 mass%, the toughness of the outer layer decreases. Therefore, when Co is added, the content is preferably 5 mass% or less. On the other hand, if Co is less than 0.1 mass%, the effect of adding Co is insufficient. The lower limit of the Co content is more preferably 0.2 mass%. The upper limit of the Co content is more preferably 4.9 mass%. One example of a more preferable range of the Co content is 0.2 to 4.9 mass%.
[0049] (5) Ti:0.01~0.5% by mass Ti combines with N and O, which are graphitization-inhibiting elements, to form oxides or nitrides. The oxides or nitrides are suspended in the molten metal and become nuclei, refining and homogenizing the MC carbides. However, if Ti exceeds 0.5 mass%, the viscosity of the molten metal increases, making casting defects more likely to occur. Therefore, when Ti is added, its content is preferably 0.5 mass% or less. On the other hand, if Ti is less than 0.01 mass%, the effect of adding Ti is insufficient. The lower limit of the Ti content is more preferably 0.02 mass%. The upper limit of the Ti content is more preferably 0.4 mass%. One example of a more preferable range of the Ti content is 0.02 to 0.4 mass%.
[0050] (6) Al: 0.001~0.5% by mass Al combines with N and O, which are graphitization-inhibiting elements, to form oxides or nitrides, which are suspended in the molten metal and become nuclei, causing fine and uniform crystallization of MC carbides. However, if the Al content exceeds 0.5 mass%, the outer layer becomes brittle, leading to deterioration of mechanical properties. Therefore, when Al is added, its content is preferably 0.5 mass% or less. On the other hand, if the Al content is less than 0.001 mass%, the effect of adding the Al is insufficient. The lower limit of the Al content is more preferably 0.01 mass%, and even more preferably 0.02 mass%. The upper limit of the Al content is more preferably 0.4 mass%. An example of a more preferable range of the Al content is 0.01 to 0.4 mass%, and even more preferably 0.02 to 0.4 mass%.
[0051] (c) Impurities The remainder of the outer layer composition is composed of Fe and impurities. P, S, Cu, etc. are impurity elements, and although the inclusion of trace amounts is unavoidable, they are known to affect graphite formation. In particular, even trace amounts of P and S are known to affect graphite. In order to obtain graphite particles with a preferred area ratio in the centrifugally cast composite roll of the present invention, it is necessary to control the content of impurity elements. In addition, since P and S cause deterioration of mechanical properties, their contents must be suppressed to a predetermined level. Cu also affects graphite, but the degree of influence in the trace range is small. Other unavoidable impurities include elements such as Ca, Ba, Mg, Sb, Te, and Ce. Specifically, the contents of P and S are each 0.1 mass% or less, Cu is 0.5 mass% or less, Ca and Ba are each 0.05 mass% or less, Mg is 0.07 mass% or less, Sb is 0.05 mass% or less, and Te and Ce are each 0.03 mass% or less, so that the effects of the present invention are hardly impaired.
[0052] (ii) organization; The structure of the outer layer of the centrifugally cast composite roll for hot rolling of the present invention is composed of a matrix, graphite, MC carbides and cementite. The structure of the outer layer in the centrifugally cast composite roll for hot rolling of the present invention preferably contains 0.3-5% graphite particles and 2-20% MC carbides on an area basis. The matrix structure of the outer layer preferably consists essentially of martensite, bainite or pearlite. The matrix structure of the outer layer preferably further contains 15-45% by area of cementite phase.
[0053] (a) Area ratio of graphite particles: 0.3-5% The area ratio of graphite particles crystallized in the outer layer structure is preferably 0.3 to 5%. If the area ratio of graphite particles is less than 0.3%, the effect of improving the seizure resistance of the outer layer is insufficient. On the other hand, if the graphite particles exceed 5 area%, the mechanical properties of the outer layer are reduced. The lower limit of the area ratio of graphite particles is more preferably 0.5%, and most preferably 1%. On the other hand, the upper limit of the area ratio of graphite particles is more preferably 4%, and most preferably 3%. An example of a more preferable range of the area ratio of graphite particles is 0.5 to 4%, and an example of a most preferable range is 1 to 3%.
[0054] (b) Area ratio of MC carbides: 2-20% If the area ratio of the MC carbide crystallized in the outer layer structure is less than 2%, the outer layer may not have sufficient wear resistance. Also, due to the coexistence with graphite, it is difficult to make the area ratio of the MC carbide exceed 20%. The area ratio of the MC carbide is more preferably 2.2% or more, and even more preferably 2.5% or more. Also, in order to make the area ratio of the graphite particles 0.3 to 5%, the MC carbide is more preferably 17% or less, even more preferably 15% or less, and most preferably 10% or less. An example of a more preferable range of the area ratio of the MC carbide is 2 to 17%, an example of a more preferable range is 2 to 15%, and an example of a most preferable range is 2 to 10%.
[0055] (B) Inner layer The iron-based alloy forming the inner layer is preferably a tough ductile cast iron (spheroidal graphite cast iron). The composition of the inner layer is represented by the composition of the iron-based alloy melt used to form the inner layer. The composition of the iron-based alloy melt corresponds to the average composition of the entire inner layer. The molten composition of the ductile cast iron is preferably C: 2.3-3.6%, Si: 1.5-3.5%, Mn: 0.2-2%, Ni: 0.3-2%, Cr: 0.05-1%, Mo: 0.05-1%, and Mg: 0.01-0.08%, with the balance being Fe and impurities. In addition to the above essential elements, Nb: 0.7% or less and W: 0.7% or less may be contained. The iron matrix of the ductile cast iron is mainly composed of ferrite and pearlite, and the rest mainly contains graphite and a small amount of cementite. An intermediate layer may be interposed between the outer layer and the inner layer for the purposes of preventing or buffering the inclusion of components.
[0056] [2] Manufacturing method of centrifugally cast composite rolls for hot rolling The centrifugally cast composite roll for hot rolling of the present invention can be produced by casting an outer layer molten metal having a chemical composition of an Fe-based alloy containing, by mass, 2.6-3.6% C, 0.1-3% Si, 0.3-2% Mn, 2.3-5.5% Ni, 0.5-3.2% Cr, 0.3-1.6% Mo, 1.8-3.4% V, and 0.7-2.4% Nb, where 1.4≦V / Nb≦2.7, V equivalent (Veq=V+0.55Nb) is 2.60-4 mass%, and the balance being Fe and impurities, at a temperature of austenite precipitation start temperature+(30-150)°C, a centrifugal force in the range of 60-200 G in gravity multiple, and an average lamination speed of 0.5-3 mm / s into a centrifugal casting die, and casting the outer layer. The lower limit of the average lamination speed is preferably 0.6 mm / s, and the upper limit is preferably 2.5 mm / s. Here, the "average lamination speed" of the outer layer is a value obtained by dividing the thickness of the outer layer formed by casting by the casting time, that is, the rate at which the thickness of the outer layer increases per unit time.
[0057] 3(a) and 3(b) show an example of a static casting mold used to cast an inner layer 2 after centrifugal casting of an outer layer 1 with a cylindrical mold 30 for centrifugal casting. The static casting mold 100 comprises a cylindrical mold 30 having an outer layer 1 on its inner surface, and an upper mold 40 and a lower mold 50 provided at the upper and lower ends of the cylindrical mold 30. The cylindrical mold 30 comprises a mold body 31, a release layer 32 formed inside the mold body 31, and mold ends 33 provided at the upper and lower ends of the mold body 31 and the release layer 32. The upper mold 40 comprises a mold body 41 and a sand mold 42 formed inside the mold body 41. The lower mold 50 comprises a mold body 51 and a sand mold 52 formed inside the mold body 51. The lower mold 50 is provided with a bottom plate 53 for holding the molten metal for the inner layer. The inner surface of the outer layer 1 in the cylindrical mold 30 has a cavity 60a for forming the trunk core portion 21 of the inner layer 2, the upper mold 40 has a cavity 60b for forming the shaft portion 23 of the inner layer 2, and the lower mold 50 has a cavity 60c for forming the shaft portion 22 of the inner layer 2. The centrifugal casting method using the cylindrical mold 30 may be any of a horizontal type, an inclined type, or a vertical type.
[0058] The cylindrical mold 30 in which the outer layer 1 has been centrifugally cast is placed upright on the upper end 54 of the lower mold 50 for forming the shaft portion 22, and an upper mold 40 for forming the shaft portion 23 is placed on top of the cylindrical mold 30, thereby forming a static casting mold 100. In the static casting mold 100, a cavity 60a in the outer layer 1 communicates with a cavity 60b in the upper mold 40 and a cavity 60c in the lower mold 50, forming a cavity 60 that integrally forms the entire inner layer 1.
[0059] After the outer layer 1 formed by centrifugal casting has solidified, the molten ductile cast iron for the inner layer 2 is poured into the cavity 60 from the upper opening 43 of the upper die 40. As the molten metal surface in the cavity 60 gradually rises from the lower die 50 to the upper die 40, the inner layer 2 consisting of the stem 22, the body core 21 and the stem 23 is cast as a single unit.
[0060] The present invention will be described in more detail with reference to examples, but the present invention is not limited thereto.
[0061] Examples 1 to 4 and Comparative Examples 1 to 4 A cylindrical mold 30 (inner diameter 800 mm, length 2500 mm) having the structure shown in Fig. 3(a) was placed in a horizontal centrifugal casting machine, and each molten metal having the composition shown in Table 1 was poured into the mold at the temperature, gravity factor, and average stacking speed shown in Table 2 to centrifugally cast the outer layer 1. After the outer layer 1 was solidified, the cylindrical mold 30 having the outer layer 1 (thickness: 90 mm) formed on the inner surface was erected, and the cylindrical mold 30 was set upright on a hollow lower mold 50 (inner diameter 600 mm, length 1500 mm) for forming the stem portion 22, and a hollow upper mold 40 (inner diameter 600 mm, length 2000 mm) for forming the stem portion 23 was set upright on the cylindrical mold 30 to form the static casting mold 100 shown in Fig. 3(b).
[0062] Molten ductile cast iron having a chemical composition containing, by mass, 3.0% C, 2.6% Si, 0.3% Mn, 1.4% Ni, 0.1% Cr, 0.2% Mo, 0.05% Mg, 0.03% P, and 0.03% S, with the remainder being Fe and impurities, was poured into cavity 60 of static casting mold 100 from upper opening 43, and a graphitized inoculant containing Si was inoculated during the pouring to produce a composite roll in which inner layer 2 is integrally welded to the inner surface of outer layer 1.
[0063] [Table 1-1] Notes: (1) Corresponds to the average composition of the outer layer.
[0064] [Table 1-2] Note: (1) Veq=V+0.55Nb (unit: mass %).
[0065] [Table 2] Note: (1) γ is the austenite precipitation temperature.
[0066] For each of the composite rolls of Examples 1 to 4 and Comparative Examples 1 to 4, the soundness of the boundary between the outer layer and the inner layer, the distribution of MC carbides in the outer layer, the wear resistance of the surface and deep parts of the outer layer, and casting defects in the outer layer were measured by the following methods.
[0067] (1) Integrity of the boundary between the outer and inner layers Defects in the outer layer were detected by an ultrasonic inspection method in which an ultrasonic probe was used to scan the entire surface of the outer layer, and the defects were evaluated according to the following criteria. ○: No defects with a diameter of 10 mm or more were present at the boundary between the outer layer and the inner layer. ×: A defect with a diameter of 10 mm or more was present at the boundary between the outer layer and the inner layer.
[0068] (2) Distribution of MC carbides in the outer layer At the longitudinal end of each outer layer, the outer layer structure was observed under a microscope at the position of the initial diameter Di (a position approximately 10 mm deep from the black surface) and at positions 10 mm, 20 mm, 30 mm, 40 mm, and 50 mm deep from the initial diameter Di, and the distribution of MC carbides was classified into patterns I to IV shown in Figure 2.
[0069] (3) Average wear resistance of the outer layer The average wear resistance of the outer layer used was judged according to the following criteria based on the V equivalent (Veq = V + 0.55Nb) distribution. ○: When the V equivalent of the molten metal composition used as the outer layer material is 2.6 or more. ×: When the V equivalent in the molten metal composition used as the outer layer material is less than 2.6.
[0070] (3) Abrasion resistance at the surface and deep parts of the outer layer The wear resistance of the surface and deep parts of the outer layer used was judged according to the following criteria based on the V equivalent (Veq = V + 0.55Nb) distribution. ×: The lowest V equivalent in each of the surface and deep parts of the layer used is less than 60% of the average V equivalent of the outer layer molten metal. △: The lowest V equivalent in each of the surface and deep parts of the layer used is 60% or more and less than 70% of the average V equivalent of the outer layer molten metal. ○: When the lowest V equivalent in each of the surface and deep parts of the layer used is 70% or more of the average V equivalent of the outer layer molten metal.
[0071] (4) Casting defects in the outer layer The presence or absence of defects in the outer layer was detected by an ultrasonic flaw detection method in which an ultrasonic probe was used to scan the entire surface of the outer layer, and the defects were evaluated according to the following criteria. ○: No casting defects with a diameter of 1 mm or more were present in the outer layer. ×: Casting defects with a diameter of 1 mm or more were present in the outer layer.
[0072] Based on the evaluation results of the soundness of the boundary between the outer layer and the inner layer, the average wear resistance of the outer layer used, and the wear resistance of the surface and deep parts, and casting defects in the outer layer, a comprehensive evaluation was made according to the following criteria. ○: All evaluation items were ○. △: There were 1 or 2 items rated as × or △ in total. ×: A total of three or more items were rated × or △.
[0073] [Table 3] Note: (1) Average abrasion resistance across all used layers of the outer layer. Note: (2) Abrasion resistance of the surface layer of the outer layer used. Note: (3) Abrasion resistance deep within the used outer layer.
[0074] As is clear from Table 3, the centrifugally cast composite rolls of Examples 1 to 4 were excellent in all of the soundness of the boundary between the outer layer and the inner layer, the wear resistance of the surface and deep parts of the outer layer, and the casting defects in the outer layer. In contrast, the centrifugally cast composite rolls of Comparative Examples 1 to 4 were evaluated as × in one or more of the above evaluation items. Specifically, in Comparative Examples 1 and 2, Veq was less than 2.60, so neither the surface nor deep parts of the outer layer had sufficient wear resistance. In Comparative Example 3, V / Nb was too high at 4.37, so the soundness of the boundary was poor. Furthermore, in Comparative Example 4, V / Nb was low at 1.23, so the distribution of MC carbides was III type, and not only was the wear resistance of the deep part of the outer layer insufficient, but casting defects were confirmed in the outer layer. [Explanation of symbols]
[0075] 1...outer layer 2. Inner layer 10. Centrifugal cast composite roll for hot rolling 21... Body core 22, 23... Shaft section 30...Cylindrical mold for centrifugal casting 31, 41, 51...Mold body 32...Release layer 33...Mold end 42,52 Sand mold 40···Upper mold for static casting 50···Lower mold for static casting 60, 60a, 60b, 60c...cavity 100···Static casting mold
Claims
1. A centrifugally cast composite roll for hot rolling, comprising an outer layer made of an Fe-based alloy having a chemical composition, on a mass basis, of 2.6-3.6% C, 0.1-3% Si, 0.3-2% Mn, 2.3-5.5% Ni, 0.5-3.2% Cr, 0.3-1.6% Mo, 1.8-3.4% V, and 0.7-2.4% Nb, with 2.01≦V / Nb≦2.7, a V equivalent (Veq=V+0.55Nb) of 2.60-4% by mass, and the remainder being Fe and impurities, and an inner layer made of ductile cast iron welded and integrated to the outer layer.
2. 2. The centrifugally cast composite roll for hot rolling according to claim 1, wherein the outer layer further contains B: 0.06% by mass or less.
3. 3. The centrifugally cast composite roll for hot rolling according to claim 1, wherein the outer layer further contains, by mass, at least one of W: 0.01-3%, Ti: 0.01-0.5%, Al: 0.001-0.5%, Zr: 0.01-0.5%, and Co: 0.1-5%.
4. 4. The centrifugally cast composite roll for hot rolling according to claim 1, wherein the V equivalent of the outer layer is 3.8 mass% or less.
5. The centrifugally cast composite roll for hot rolling according to any one of claims 1 to 4, characterized in that the outer layer contains 0.3 to 5% graphite particles and 2 to 20% MC carbide on an area basis.
Citation Information
Patent Citations
Roll for rolling and its production
JP1992350143A
Composite sleeve for roll for rolling wide flange shape
JP1997209073A
Roll for hot rolling made by centrifugal casting
JP2001279367A
External layer material of roll for hot rolling and composite roll for hot rolling
JP2004068142A
External layer material for composite roll for rolling made by centrifugal casting
JP2008050681A